Ventricular septal defect Doppler peak gradient underestimates right ventricular systolic pressure in the presence of right bundle branch block - Santosh C Uppu; Shubhika Srivastava; Barry A Love (Wolters Kluwer Medknow Publications, 2022)
Estimation of the right ventricular systolic pressure (RVSP) using echocardiographically derived maximal instantaneous gradient across the ventricular septal defect is a well-utilized tool, which can potentially underestimate the RVSP in patients with conduction abnormalities as such its utility in these patients is questionable.